2020
DOI: 10.3390/rs12132151
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Groundwater Storage Changes in Two Main Grain Producing Areas in China: Implications for Sustainable Agricultural Water Resources Management

Abstract: Balancing groundwater supply and food production is challenging, especially in large regions where there is often insufficient information on the groundwater budget, such as in the North China Plain (NCP) and the Northeast China Plain (NECP), which are major food producing areas in China. This study aimed to understand this process in a simple but efficient way by using Gravity Recovery and Climate Experiment (GRACE) data, and it focused on historical and projected groundwater storage (GWS) changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 55 publications
3
13
0
1
Order By: Relevance
“…IWC increased in HHH because of the lack of precipitation, leading to the water storage deficit getting more serious during 2003-2014, according to Figures 5, 6 and 8. This indicated that under the superposition of poor precipitation and increased IWC, water storage reduction and water storage deficit were further aggravated, especially in HHH [43]. Thus, we suggest that the structure of agricultural planting in HHH should be adjusted to reduce the water consumption for irrigation in winter.…”
Section: Discussionmentioning
confidence: 92%
“…IWC increased in HHH because of the lack of precipitation, leading to the water storage deficit getting more serious during 2003-2014, according to Figures 5, 6 and 8. This indicated that under the superposition of poor precipitation and increased IWC, water storage reduction and water storage deficit were further aggravated, especially in HHH [43]. Thus, we suggest that the structure of agricultural planting in HHH should be adjusted to reduce the water consumption for irrigation in winter.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, the productivity of land has been significantly increased and the grain yield has increased rapidly. However, while increasing grain production, a series of ecological and environmental problems have arisen, such as groundwater overdraft in North China and non-point source pollution caused by the use of chemical fertilizers and pesticides [ 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The North China Plain, located in the eastern coastal region of China, lies between latitude 35° N–41° N and longitude 113° E–120° E ( Figure 1 ). It is one of the three great plains in China, covering an area of approximately 140,000 km 2 [ 48 ]. The NCP is a central agricultural area in China, which produces about one-fourth of the country’s total grain yield [ 10 ].…”
Section: Study Area and Datamentioning
confidence: 99%